2017
DOI: 10.7150/ijms.20387
|View full text |Cite
|
Sign up to set email alerts
|

EMMPRIN Inhibits bFGF-Induced IL-6 Secretion in an Osteoblastic Cell Line, MC3T3-E1

Abstract: Background: Electrolytically-generated acid functional water (FW) is obtained by electrolyzing low concentrations of saline. Although it has been widely used in clinical practice with various purposes, the underlying mechanisms of action involved have not been fully elucidated so far. We used the human cervical cancer-derived fibroblastic cell line (HeLa), to examine the cytokine secretion profile following FW treatment in the present study.Results: FW stimulation significantly induced the secretion of basic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…To date, the biological effects of FW have been investigated using cell culture. In HeLa cells, FW stimulation induced the secretion of bFGF into the culture media (Saiki et al, ). The secreted bFGF has been shown to augment the expression of VEGF in fibroblasts (Yanagita et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the biological effects of FW have been investigated using cell culture. In HeLa cells, FW stimulation induced the secretion of bFGF into the culture media (Saiki et al, ). The secreted bFGF has been shown to augment the expression of VEGF in fibroblasts (Yanagita et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The induction of these genes might be due to the effect of bFGF. In fact, stimulation of murine osteoblastic cell, MC3T3‐E1 cells, with recombinant FGF induced the secretion of VEGF (Saiki et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrolytically-generated acid functional water (FW), obtained by electrolyzing low concentrations of saline, is widely used as a disinfectant, in clinical practice 9 . In a previous report, FW was demonstrated to augment basic fibroblast growth factor (bFGF) secretion in HeLa cells 10 . As FW-treatment significantly induced the secretion of lactate dehydrogenase (LDH), a marker of cell damage, it was expected to cause some amount of damage to the cells.…”
Section: Introductionmentioning
confidence: 95%
“…Acid‐electrolyzed functional water (FW) is obtained by the electrolysis of sodium chloride solution, and is widely used as a disinfectant in clinical practice . In an attempt to elucidate the biological effects of FW, the human fibroblast cell line HeLa was treated with FW and cytokine secretion profiles were examined . The results indicated that FW significantly induced bFGF secretion.…”
Section: Introductionmentioning
confidence: 99%